Gliptin Wars - Canavan, Neil (MD Conference Express, 2008)
Following closely behind vildagliptin and sitagliptin, the two currently marketed compounds in the DPP-IV inhibitor drug class, are the pipeline agents saxagliptin and alogliptin. This article discusses data concerning all four molecules.